Frecuencia de diarreas, evaluación de la presencia de Cryptosporidium spp y su relación con el nivel de proteínas plasmáticas en terneros de la granja san Pedro de la UAN (2020)
Neonatal bovine diarrhea (DBN) is a complex and multifactorial disease that frequently affects calves due to its associated risk factors, such as the condition agammaglobulinemic at birth and the failure in the transfer of passive immunity. In order to contribute to the execution of studies and to evaluate the amount of diarrhea presented at the San Pedro Farm of the UAN, a study was carried out to verify the frequency of diarrhea, evaluate the presence of Cryptosporidium spp and relate diarrhea to the level of total plasma 5 proteins in calves, A total of 13 calves were evaluated and blood samples were taken (to evaluate total plasma proteins) and 10-week serial coprological (to assess the presence of oocysts by modified Ziehl Neelsen staining). Diarrhea was classified as: Mild, moderate and severe, where the greatest presence of diarrhea (mild and moderate) occurred in the first two weeks of birth of the calf, but no oocysts of Cryptosporidium spp were found, in terms of plasma proteins 11 of the 13 calves sampled were within range as an excellent immunity transfer (> 5g/dl).